Prevalent vaccination practices among Indian Allopathic non-pediatrician doctors for their own children: A proxy indicator of updated knowledge about childhood immunization - Priyanka Gupta; Mitasha Singh; Shailja Sharma; Ranabir Pal (Al Ameen Medical College, 2017)
Background: It has been hypothesized that the general physicians and specialists other than pediatricians operating in the private sectors of India do not access regular updates about the newer, and additional vaccines i.e., non-national schedule vaccines. Objective: To learn the vaccination practices of allopathic doctors operating in private sector of India followed by them in their own children, which could serve as a proxy indicator of their knowledge about childhood immunization. Methodology: This cross-sectional study was conducted among non-pediatrician and non-specialist Allopathic doctors practicing in Indian private sector, whose last borne child was more than or equal to three and less than 4.5 years of age using an online semi-structured questionnaire. We received valid responses from 49 doctors from Delhi, Uttar Pradesh, Himachal Pradesh and Bihar, within a span of 30 calendar days. Results: Compliance with BCG and DPT was 100%. Around 92% babies were completely vaccinated with Oral polio drops (five doses). For rest of the UIP vaccines, including Hepatitis-B, HiB, Measles and Measles Mumps and Rubella combination vaccine; the coverage was poor ranging from 43-86%. Additional vaccines like IPV, Rotavirus, PCV, Varicella, Hepatitis-A and Typhoid were given only in a few of the children; maximum coverage for rotavirus vaccine (42.86%) and minimum for Hepatitis-A (4.00%). Conclusion: It could be commented that the complete immunization till date even for the UIP vaccines was nothing better in the children of doctors when compared with the national statistics. It is also likely that at times doctors are unaware of the newer and additional vaccines and their importance in vaccination schedule (presuming cost is not a limiting factor for them).